Filmes ativos de pectina e compostos fenólicos da casca da manga para aplicação em embalagens de alimentos - Ribeiro, Ana Carolina Barbosa (2022)
This work aimed to develop active films of pectin and phenolic compounds using mango peels, Tommy Atkins variety, which are considered an agro-industrial residue in the fruit processing. The matrix used was pectin, isolated and characterized by Infrared Spectroscopy (FTIR), Thermal Analysis (TGA and DSC), Hydrogen and Carbon Nuclear Magnetic Resonance (1H and 13C NMR) and Gel Permeation Chromatography (GPC). Pectin showed good thermal stability, satisfactory yield, high degree of methoxylation and molar mass in the order of 106 g mol-1. The aqueous, ethanolic and methanolic extracts were obtained with yields varying between 17 and 33%. The extracts showed a variety of phenolic compounds that were identified by the UPLC-MS analysis, and a high content of total phenolics quantified by the Folin-Ciocalteau method. The extracts were evaluated for their antioxidant activities through ABTS and DPPH tests and for their antimicrobial activities against Escherichia coli, Salmonella enteritidis, Listeria monocytogenes and Staphylococcus aureus bacteria. The ethanolic and methanolic extracts showed higher antioxidant activity and were more effective in inhibiting the growth of Gram-positive and Gram-negative bacteria. In general, the films containing phenolic extracts characterized in terms of opacity, Water Vapor Permeability (WVP), antioxidant activity, mechanical and thermal properties, presented better results than those obtained for the control film (without the presence of phenolics). Therefore, the films developed in this work present themselves as a promising alternative for application as packaging and/or active coatings for food.